ANALISIS KESESUAIAN STANDAR PELAYANAN KEFARMASIAN DI UPT. PUSKESMAS BAQA KOTA SAMARINDA BERDASARKAN PERMENKES RI - Mochammad Tri Norcahyo; Adhe Septa Ryant A; Raymon Simanullang (Bajang Institute, 2025)
Pharmaceutical services at community health centers are an integral part of the implementation of health efforts which play an important role in advancing the quality of health services for the community. To support this, the standard of pharmaceutical services at community health centers has undergone several changes and was most recently updated with Minister of Health Regulation No. 26 of 2020 concerning Pharmaceutical Service Standards at Community Health Centers. The aim of this research is to determine the suitability of implementing pharmaceutical service standards at the Baqa Health Center, Samarinda City. This research uses an observational method with a descriptive approach using a checklist sheet with suitability guidelines based on the Indonesian Minister of Health Regulation. This research was conducted in the period September 2024 – December 202 The research results showed that the suitability of pharmaceutical services at the Baqa Community Health Center was in accordance with the Indonesian Minister of Health's Regulation with a result of 86.6% in the good category. The management of pharmaceutical preparations and consumable medical materials as well as facilities and infrastructure at the Baqa Community Health Center is in accordance with the technical instructions for pharmaceutical service standards, while clinical pharmacy services at the Baqa Community Health Center are in accordance with the technical instructions for pharmaceutical service standards